Path Loss Model Optimization In An Urban Environment Using Genetic Algorithm - Anwar Faizd Osmanc, Mohamad Huzaimy Jusohd, Lee Loo Chuana, Mardeni Rosleea, Chilakala Sudhamania, Athar Waseemb (International Journal of Intelligent Systems and Applications in Engineering, 2024)
An essential requirement for the design of a wireless communication system is the determination of the path loss. This article compares and estimates path loss using urban macro environment path loss models. Path loss model optimization is taken into consideration to represent the real propagation path and to find the optimized path loss model using a genetic algorithm. The analytically measured path loss is contrasted with the optimized path loss values of each model and error statics are used to assess each model’s performance. From the results, it can be deduced that the 5GCM LOS and NLOS model generates the mean square error and standard deviation with the lowest values. This model allows to improve the accuracy by 90.30%. The 5G heterogeneous network operators can improve the service quality at millimeter wave frequencies by employing 5GCM path loss model.